A study on the experiences of individuals who have siblings with autistic challenges: the case of Pathways Autism Trust. - Mufambisi, Ashley (Midlands State University, 2019)
This study sought to explore the experiences of siblings with a brother or sister with autistic challenges, for the presence of such a challenge in one child can affect the sibling experiences perhaps bringing them close together or pushing them further apart. The researcher observed that little is known when it comes to the sibling’s experiences when one has autism though it is of heightened importance, so this dissertation sought to bridge this gap. This is a qualitative study using a phenomenological research design; the 7 participants of this study were purposefully selected using the heterogeneous sampling and they were 16 years of age and above. Data was analysed by the content analysis, which is a procedure of verbal categorization of verbal behavioural data for purposes of classification, summarization and tabulation. Several themes and subthemes emerged from this study the negative challenges faced by the siblings being embarrassment, being a young carer and future caregiver and lack of attention. The positive experiences included an improvement in their leadership skills, personal enrichment and psychological growth. The coping strategies they used were support groups, therapy sessions and avoiding unnecessary physical and emotional pressure. Conclusively, the researcher brought out both the negative and positive experiences faced by siblings of autistic individuals and how they cope. The researcher recommended a further enlightment on autism so as to lessen the challenges that are faced by the siblings of autistic individuals.